PELAKSANAAN TANGGUNG JAWAB PELAKU USAHA PERHOTELAN TERHADAP BARANG MILIK TAMU HOTEL DI MAKASSAR (STUDI KASUS WHIZ PRIME SUDIRMAN): IMPLEMENTATION OF RESPONSIBILITIES OF HOTEL BUSINESSES FOR HOTEL GUEST GOODS IN MAKASSAR (CASE STUDY WHIZ PRIME SUDIRMAN) - Laydida, Evelyn Meilinda; Hamid, Abd. Haris; Kamsilaniah (Clavia, 2020)
The purpose of this study is to determine the implementation of the responsibilities of hoteliers in the Whiz Prime Hotel Sudirman Makassar and to know the terms of service for the safety of guest goods while staying at the hotel. The research was conducted at Whiz Prime Hotel Sudirman which is located in Makassar, with the field throught the process of the interviews or direct conversations the Hotel Manager and guest whi stay overnight, and also the library research method. This method is efforts to obtain secondary trought reading materials in the form of scientific writings laws and regulation theories of expert throught various media. The results of this study indicate that the provision of service to guests is in accordance with the standard operating procedures (SOP) that have been set by the company, but in this case the company or hoteliers are inconsistent in carrying out the rules that have been set so that guest items are lost which causes the guest felt insecure and at a disadvantage by the incident so that the guest did not get his rights as a consumer based on Article 4 of Law no. 8 of 1999 concerning consumer rights. In this case, the business actor is already responsible for compensation to the guests based on Article 19 of Law no. 8 of 1999 concerning the responsibilities of business actors, but the business actor explains and resolves the problem to guests who feel disadvantaged by not providing an accurate explanation. In handling it, the hoteliers have carried out their responsibilities in the process of compensating guests who suffered losses for the loss of items in the form of gold and watches. The responsibility of hotel entrepreneurs for the loss of property belonging to room tenants is the responsibility of Whiz Prime Hotel Sudirman applies in accordance with Article 1545 of the Civil Code and Article 19 paragraphs (1), (2), (3) and paragraph (4) of UUPK, but in its implementation Whiz Prime Hotel Sudirman provides compensation to consumers who suffer losses, this is done to maintain the trust of hotel guests even though the compensation given does not always match the amount of loss suffered by hotel guests. Responsibility for damage and loss of items experienced by hotel guests, is not solely the responsibility of the hotel, if the damage or loss experienced by the guest is due to negligence on the part of the hotel, then it is the responsibility of the hotel, and vice versa. If damage and loss is experienced due to negligence on the part of the guest, it is not the responsibility of the hotel but the guest himself. If the damage or loss is due to negligence of the hotel, the hotel will immediately take compensation measures, namely in the form of money in accordance with the provisions that the hotel and guests feel are disadvantaged.